The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/ar.21449
|View full text |Cite
|
Sign up to set email alerts
|

Functional Anatomy and Adaptation of Male Gorillas (Gorilla gorilla gorilla) With Comparison to Male Orangutans (Pongo pygmaeus)

Abstract: Great apes diversified during the Miocene in Old World forests. Two lineages, gorillas in Africa and orangutans in Asia, have sexual dimorphisms of super-sized males, though they presumably diverged from a smaller common ancestor. We test the hypothesis that they increased in body mass independently and convergently, and that their many postcranial differences reflect locomotor differences. Whole body dissections of five adult male gorillas and four adult male orangutans allowed quantification of body mass dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 84 publications
3
51
0
Order By: Relevance
“…Individual paniscus female 3 (PF3) had no offspring or pregnancies during her life, had remarkably low levels of dissectible fat, and stood out as having the highest percentage of muscle mass among the females (44.1%, Table 1). Body fat is also sexually dimorphic in some monkeys, as well as in gorillas and orangutans (23)(24)(25), and has a demonstrated role in reproduction (54)(55)(56). The same is true for H. sapiens (19,(43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Individual paniscus female 3 (PF3) had no offspring or pregnancies during her life, had remarkably low levels of dissectible fat, and stood out as having the highest percentage of muscle mass among the females (44.1%, Table 1). Body fat is also sexually dimorphic in some monkeys, as well as in gorillas and orangutans (23)(24)(25), and has a demonstrated role in reproduction (54)(55)(56). The same is true for H. sapiens (19,(43)(44)(45)(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Skin. African apes' hairy skin constitutes between 10% and 16% of their total body mass (24,25). Long hair shafts and follicles grow in a relatively thick epidermis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural differences between the forelimbs and the hindlimbs have been well documented among vertebrates; the pectoral girdle is generally more mobile than the pelvic girdle and structural differences between the glenoid cavity and the acetabulum lead to the potential for a greater range of motion in the forelimb than in the hindlimb (Haines, 1952;Snyder, 1954;Peterson, 1971;Peterson, 1973;Peterson, 1974;Jenkins and Goslow, 1983;Peterson, 1984;Reynolds, 1985;Schmitt, 1994;Larson et al, 2001;Lammers, 2007;Zihlman et al, 2011). In most primates, the shallow glenoid cavity with reduced coracoid and acromion processes in the pectoral girdle compared with the deeper acetabulum of the pelvic girdle are likely related, in part, to the greater weightbearing function of the hindlimbs relative to the mobile forelimbs (Reynolds, 1985;Zihlman et al, 2011). These structural differences between forelimbs and hindlimbs tend to be most exaggerated in arboreal species, including primates (Larson et al, 2000), with some of the most extreme examples found in lizards.…”
Section: Introductionmentioning
confidence: 99%